Relation between ultrasound and carcass measures in buffaloes slaughtered in different stages of feedlot - Andrighetto, C. [UNESP]; Jorge, A. M. [UNESP]; Francisco, C. L. [UNESP]; Pinheiro, R. S.B. [UNESP]; Santos Silva, T. L. [UNESP]; Surge, C. A. [UNESP]; Andrade, C. R.M. [UNESP]; Tavares, S. A. [UNESP]; Puoli Filho, J. N.P. [UNESP] (My University, 2010)
The ultrasound is used as a tool to estimate the ribeye area and backfat thickness. The purpose of this work was to evaluate the correlations between the measures obtained by ultrasound and carcass as well as follow the development of the ribeye area and backfat thickness of buffaloes in different stages of feedlot. Twenty castrated, hornless, Murrah buffaloes were used. The buffaloes were separated in four groups that were slaughtered in 75, 100, 125, 150 days of feedlot. The measures taken by ultrasound when the buffaloes reached the slaughter point and in carcass after the slaughter were ribeye area and backfat thickness. The backfat thickness was evaluated with the paquimeter and the ribeye area was obtained with the use of a quadrant grade ruler. The ribeye area and backfat thickness presented linear increase effect in function of the stages of feedlot. The linear increase from 75 to 150 days of feedlot for ribeye area and backfat thickness presented that buffaloes hadn't reached maturity. The correlations measured by ultrasound and carcass were. 82 for ribeye area and .85 for backfat thickness. The characteristics of the measures by ultrasound, in buffaloes, presented good correlations with measures at the moment of slaughter, that enable to follow the alterations of this traits in Murrah buffaloes castrated of herd milk during their development.
Keywords: Fat thickness; Ribeye area; Water buffaloes